Pengaruh Model Pembelajaran Berbantuan Multimedia Terhadap Hasil Belajar Matematika: Ditinjau Dari Gaya Belajar Siswa SD - Idris, Muhamad; Suroyo, Suroyo; Saabighoot, Yus Alvar; Houtman, Houtman (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
The study was conducted to determine the effect of multimedia-assisted learning models on mathematics learning outcomes based on learning styles in fifth grade students in Cisoka District. The population is 165 fifth grade students at SDN Jeungjing I, II and III while the research sample is 74 students. Research instruments in the form of questionnaires and tests. The first hypothesis is the value of Fcount = 199.36 and the value of Ftable = 3.97, the second hypothesis is the mean value of the experimental class analytical learning style is 44 with a standard deviation of 1.854, while the global learning style is 11 standard deviations of 2.278, the third hypothesis is the Fcount = 137 .16 and the value of Ftable = 4.13, the fourth hypothesis the value of Fcount = 454.59 and the value of Ftable = 4.13, the fifth hypothesis the value of Fcount = 601.183, the value of Ftable = 3.91. The results of the analysis show the effect of multimedia-assisted learning models on mathematics learning outcomes based on the learning styles of fifth grade students in Cisoka District.